2009
DOI: 10.1002/eqe.905
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐plastic hinge design concept for reducing higher‐mode effects on high‐rise cantilever wall buildings

Abstract: SUMMARYThis paper explores the notion of detailing reinforced concrete structural walls to develop base and midheight plastic hinges to better control the seismic response of tall cantilever wall buildings to strong shaking. This concept, termed here dual-plastic hinge (DPH) concept, is used to reduce the effects of higher modes of response in high-rise buildings. Higher modes can significantly increase the flexural demands in tall cantilever wall buildings. Lumped-mass Euler-Bernoulli cantilevers are used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 10 publications
1
65
0
1
Order By: Relevance
“…In the considered systems, beam does not exist and the post-tensioned slab transfers the gravity load to the columns. The insigni cant e ect of the perimeter columns and this kind of slabs subjected to lateral load has been demonstrated by other research studies [1,2,14,21]. Therefore, the RC core-wall undergoes all the seismic lateral loads applied to the building.…”
Section: Design Of High-rise Rc Core-wall Buildingsmentioning
confidence: 74%
See 3 more Smart Citations
“…In the considered systems, beam does not exist and the post-tensioned slab transfers the gravity load to the columns. The insigni cant e ect of the perimeter columns and this kind of slabs subjected to lateral load has been demonstrated by other research studies [1,2,14,21]. Therefore, the RC core-wall undergoes all the seismic lateral loads applied to the building.…”
Section: Design Of High-rise Rc Core-wall Buildingsmentioning
confidence: 74%
“…For SPH cases in which the plastic hinge region occurred at the base of the wall, an inelastic shear wall section was used for the lowest 10% of the core-wall height adjacent to the foundation [14]. It was assumed that the upper regions would remain elastic; therefore, in the upper levels, elastic shear wall elements were used.…”
Section: Nonlinear Modeling 31 Fiber Element Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the effect of higher dynamic modes and their contribution in response to structure are not negligible, particularly in long period structures both in linear and nonlinear behaviors [42][43][44]. The higher mode effects increase the action demands at mid-height of shear walls.…”
Section: Bending Moment Responsementioning
confidence: 99%